2019
DOI: 10.1371/journal.pone.0214808
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pneumoconiosis by serum and urinary biomarkers in workers exposed to asbestos-contaminated minerals

Abstract: Workers processing nephrite, antigorite, or talc may be exposed to paragenetic asbestos minerals. An effective screening method for pneumoconiosis in workers exposed to asbestos-contaminated minerals is still lacking. The objective of this study was to assess the diagnostic accuracy of serum and urinary biomarkers for pneumoconiosis in workers exposed to asbestos-contaminated minerals. We conducted a case-control study in a cohort of stone craft workers in Hualien, where asbestos, nephrite, antigorite, and tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Measuring 8-OHdG concentrations in white blood cells 25,26) and urine 27,28) of occupationally asbestos-exposed individuals is useful for assessing oxidative DNA damage. We have also reported that 8-OHdG effectively assesses lung injury (sustained inflammation) caused by chrysotile 21) .…”
Section: Evaluation Of Peritoneal Mesothelioma By the Ip Injection Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring 8-OHdG concentrations in white blood cells 25,26) and urine 27,28) of occupationally asbestos-exposed individuals is useful for assessing oxidative DNA damage. We have also reported that 8-OHdG effectively assesses lung injury (sustained inflammation) caused by chrysotile 21) .…”
Section: Evaluation Of Peritoneal Mesothelioma By the Ip Injection Of...mentioning
confidence: 99%
“…More research is needed to conclude mesothelioma carcinogenesis concerning heating products of chrysotile. Currently, the technique for the clinical diagnosis of malignant mesothelioma caused by chrysotile exposure has advanced, and tests for 8-hydroxy-2′-deoxyguanosine (8-OHdG) [25][26][27][28] , serum N-ERC/mesothelin 29,30) , and CDKN2A/p16 gene 31,32) deletion have been reported to be effective. Therefore, these testing techniques may be useful for evaluating mesothelioma carcinogenesis using chrysotile heating products.…”
Section: Introductionmentioning
confidence: 99%
“…Several influential media reports were publicized. Among them, those arousing the most heated discussions was a report on the miserable living condition of rural migrant workers who suffered from pneumoconiosis (Yang 2009). To pacify the public anger, the state later incorporated the "pay in advance" suggestion in the Social Insurance Law.…”
Section: State's Initial Attempt At Institutionalizing Ngosmentioning
confidence: 99%
“…There are several reviews on pneumoconiosis among coal miners; most of them discussed the prevalence, risk factors, survival rate, and prevention of CWP based on the pathological findings [ 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The past CAD studies of CWP disease indicate no significant review of machine learning applications that might help improve future work in the area.…”
Section: Introductionmentioning
confidence: 99%